2021
DOI: 10.1089/acm.2020.0392
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Physician Treatment Recommendations and Compliance Among U.S. Adults with Low Back Pain

Abstract: Objectives: Numerous recently published clinical care guidelines, including the 2017 American College of Physicians (ACP) Guideline for Low Back Pain (LBP), call for nonpharmacological approaches to pain management. However, little data exist regarding the extent to which these guidelines have been adopted by patients and medical doctors. The study objective was to determine patient-reported treatment recommendations by medical doctors for LBP and patient compliance with those recommendations.Design: This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
(28 reference statements)
0
18
2
Order By: Relevance
“…4 In a 2018 survey, 27.0% of LBP patients reported being recommended BZDs by a medical doctor in the previous 12 months. 26 As adjuvant analgesics, 22 27 BZDs have been used to treat LBP-related muscle spasms 23 28 and neuropathic pain. 24 28 Although early research suggested BZDs had a direct analgesic effect related to central or peripheral receptormediated interactions, 24 29 there has not been conclusive evidence that BZDs produce an overall analgesic effect.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…4 In a 2018 survey, 27.0% of LBP patients reported being recommended BZDs by a medical doctor in the previous 12 months. 26 As adjuvant analgesics, 22 27 BZDs have been used to treat LBP-related muscle spasms 23 28 and neuropathic pain. 24 28 Although early research suggested BZDs had a direct analgesic effect related to central or peripheral receptormediated interactions, 24 29 there has not been conclusive evidence that BZDs produce an overall analgesic effect.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Low back pain is often managed by primary care providers with medication recommendations to include non-steroidal anti-inflammatory drugs (NSAIDs), acetaminophen, and opioids [6][7][8]. Primary care providers, in concordance with clinical practice guidelines (CPG), also encourage non-pharmacological LBP care to include patient education, remaining physical active, and manual therapies.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 However, paracetamol remains one of the most commonly used analgesics to manage LBP worldwide, with between 50% and 95% of LBP sufferers across Australia, USA and Europe taking paracetamol. [3][4][5][6][7][8][9] In Australia, this represents a heavy economic burden on individuals and society, as approximately $1 billion dollars per annum spent on LBP treatment is associated with analgesics such as paracetamol. 10 Previous studies have highlighted that consumers lack knowledge and understanding regarding the possible harms when taking paracetamol, with up to…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many international clinical guidelines in the USA, UK, Germany, Denmark and Belgium no longer recommend the use of paracetamol (acetaminophen) for individuals with low back pain (LBP) due to the lack of clinical benefits and emerging links with adverse events associated with the medication 1 2. However, paracetamol remains one of the most commonly used analgesics to manage LBP worldwide, with between 50% and 95% of LBP sufferers across Australia, USA and Europe taking paracetamol 3–9. In Australia, this represents a heavy economic burden on individuals and society, as approximately $1 billion dollars per annum spent on LBP treatment is associated with analgesics such as paracetamol 10.…”
Section: Introductionmentioning
confidence: 99%